Robo Escape (Survival Statics): Development Of A Third Person Shooter 3d Game To Learn Statics - Muhammad Wildan, Mohd Azman (2023)
Game is structured form of play, typically undertaken for enjoyment and sometimes used as an educational tool. It is created primarily for the purpose of providing entertainment to the players. While educational game is a game designed to teach players a specific subject or skill in an entertaining way. Majority of the educational game today is focusing more on the educational part than the entertain part. This makes the game not balance. By combining educational and normal game together, this will make the educational part way more engaging and interactive. Therefore, the main purpose of this project is to develop an educational game that is effective to the students. Besides, engaging and interactive learning in gaming could potentially stimulate student’s interest of learning. Rapid Application Development (RAD) method has been chosen in development of this application. There were seven phases involved in the model to make sure that the designing and developing of the application has achieves the proposed objective. The application was evaluated by university and high-school students and lecturers to investigate its effectiveness. The result shoed that users give positive feedback and agreed that had achieved its objective to evaluate the effectiveness and functionality.